“IN PAIN” HISTORY OF DENTAL DISEASE DALAM KARYA FOTOGRAFI STILL LIFE - Sarsono, Nurmanita; Wahyudi, Johan Ies (TEXTURE Art and Culture Journal, 2024)
“IN PAIN” History of Dental Disease in photography is the idea of ​​the final project to represent the history of toothache experienced by the artist. Through the medium of still life photography, the creation of this work will raise objects related to toothache. Still-life photography is usually made in a studio setting where the artist uses the right composition and lighting to display the shape, show the surface quality of the object, build a mood, and draw the audience's attention to certain elements, by using Ferdinand de Saussure’s semiotic approach in selecting objects so that they can be present symbolically, conveying a strong narrative and message for the connoisseur of the work. The choice of presentation of the work uses a still-life photography approach with artificial light techniques to visualize events. Artificial light is used to freely adjust the direction of incoming light and which parts need to be illuminated. The artist uses a softbox and studio strobe light as lighting tools because they are easy to move and maneuver. Softboxes are used to shoot several works that require smooth and even lighting, so the resulting shadows look relatively soft and even. Meanwhile, studio strobe light is used in shooting several works that require hard or strong lighting, so that the resulting shadows also look relatively strong and clear to maximize the texture and dimensions of the object.